1977
DOI: 10.1093/genetics/85.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Regions of Stable Equilibria for Models of Differential Selection in the Two Sexes Under Random Mating

Abstract: The equilibrium structure of models of differential selection in the sexes is investigated. It is shown that opposing additive selection leads to stable polymorphic equilibria for only a restricted set of selection intensities, and that for weak selection the selection intensities must be of approximately the same magnitude in the sexes. General models of opposing directional selection, with arbitrary dominance, are investigated by considering simultaneously the stability properties of the trivial equilibria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(86 citation statements)
references
References 3 publications
3
82
1
Order By: Relevance
“…SSDRs can greatly broaden the parameter space for which SA selection can maintain balanced polymorphisms (Kidwell et al. 1977 ; Fry 2010 ; Connallon and Clark 2011 , 2012 ). SSDRs can arise through two distinct mechanisms, either as a by‐product of concavity of fitness landscapes and SA selection (see fig.…”
Section: Discussionmentioning
confidence: 99%
“…SSDRs can greatly broaden the parameter space for which SA selection can maintain balanced polymorphisms (Kidwell et al. 1977 ; Fry 2010 ; Connallon and Clark 2011 , 2012 ). SSDRs can arise through two distinct mechanisms, either as a by‐product of concavity of fitness landscapes and SA selection (see fig.…”
Section: Discussionmentioning
confidence: 99%
“…When fitness effects of SA alleles are small [ 19 , 51 ], single-generation allele frequency changes at X-linked and autosomal loci (respectively) are well-approximated by and (see the electronic supplementary material). SA selection is expected to maintain genetic variation (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…And hence if we let the frequency of gametes A 1 , A 2 be x t , 1 − x t in sperm and y t , 1 − y t in eggs, then in the mating pool for the following generation the frequencies of male allele A 1 s and female allele A 1 s are [7,43] x…”
Section: The Model Of Evolutionary Dynamicsmentioning
confidence: 99%
“…To plot the figures we have considered that different alleles are favored in the two sexes. If, in spite of different alleles, same alleles are favored in the two sexes, then it can be shown that the possibility of existence of equilibrium at the Mendelian segregation is low where in most of the cases the Mendelian segregation point becomes a boundary point of the stable or unstable regions [43,45]. Here, it is noticeable observation that when alleles A 1 are favored in the both sexes, the shaded region relating to feasible solution in (k, κ) space tries to spread toward the (0, 0) corner and on the contrary when the both sexes favor alleles A 2 , the shaded region tries to spread toward the opposite corner, (1,1).…”
Section: Population Genetics In Evolutionary Game Theory Frameworkmentioning
confidence: 99%